Impact of the Panama Canal expansion on Latin American and Caribbean ports: Difference in difference (DID) method - Kahuina Miller; Tetsuro Hyodo (Journal of Shipping and Trade (JST), 2021)
The expanded Panama Canal opened on June 26, 2016. This expansion is the third set of locks that enabled the canal to double its capacity through the addition of new traffic lanes, which allowed neo-Panamax and some post-Panamax vessels to transit across the canal. The widening of the canal has increased maritime traffic within Latin America and the Caribbean (LAC). Major ports in the regions have made huge investments in port expansion and infrastructural development to accommodate neo-Panamax vessels. In this study, we investigated the impact of the Panama Canal expansion (PCE) on the Latin America and the Caribbean (LAC) ports by using the Difference in Difference (DID) method. This impact was evaluated for 100 major and regular ports within the three sub-regions of LAC, namely Caribbean, Central, and South America, before and after the treatment effect, that is, the PCE. The findings from the model revealed that the average container port throughput (TEUs) for the treated ports (DTrp) was more than that of the controlled ports (CONTp) with transshipment hub, Central America, and South America having 20%, 12%, and 34% growth, respectively, since the PCE (the treatment) except for the Caribbean ports (DTrp), which experienced losses of 8% within the LAC region from 2010 to 2019.
Keywords: 650; Difference in differences (DID); Maritime traffic; Neo-Panamax vessels; Panama Canal